Selection Criteria for Lung Transplantation: Controversies and New Developments - Beeckmans, Hanne; Bos, Saskia; Vos, Robin (Seminars in Respiratory and Critical Care Medicine, 2021)
Lung transplantation is an accepted therapeutic option for end-stage lung diseases. The imbalance between limited availability and vast need of donor organs necessitates careful selection of recipient candidates, ensuring the best possible utilization of the scarce resource of organs. Nonetheless, possible lung transplant candidates who could experience a meaningful improvement in survival and quality of life should not be excluded solely based on the complexity of their case. In this review, controversial issues or difficult limitations for lung transplantation, and new developments in recipient selection criteria, are discussed, which may help broaden recipient eligibility for lung transplantation without compromising long-term outcomes.
Keywords: lung transplantation; indication; contraindication; donor selection; recipient selection; selection criteria